2021
DOI: 10.1007/s10551-021-05013-w
|View full text |Cite
|
Sign up to set email alerts
|

Change in Rhetoric but not in Action? Framing of the Ethical Issue of Modern Slavery in a UK Sector at High Risk of Labor Exploitation

Abstract: This article shows how the ethical framing of the contemporary issue of modern slavery has evolved in UK construction, a sector in which there is a high risk of labor exploitation. It also examines how these framing dynamics have inhibited the emergence of a common framework of action to deal with the issue. We draw on both framing theory and the literature on the discursive construction of moral legitimacy. Our longitudinal analysis reveals that actors seeking to shape the debate bring their own moral schemes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 103 publications
0
18
0
Order By: Relevance
“…Lawrence et al, 2009), the social movement may be curbed and even driven back in its market coverage and eventually be erased by those with vested interests in the previous status quo. Gutierrez-Huerter et al (2023) give an account for the UK construction sector of how dominant actors may forestall the emergence of new patterns of action to eradicate modern slavery and preserve the status-quo. The time it takes to convince enough actors and reach the tipping point of institutional normalization can therefore be crucial considerations for successfully establishing a market-driven socially sustainable supply chain improvement like the FFP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lawrence et al, 2009), the social movement may be curbed and even driven back in its market coverage and eventually be erased by those with vested interests in the previous status quo. Gutierrez-Huerter et al (2023) give an account for the UK construction sector of how dominant actors may forestall the emergence of new patterns of action to eradicate modern slavery and preserve the status-quo. The time it takes to convince enough actors and reach the tipping point of institutional normalization can therefore be crucial considerations for successfully establishing a market-driven socially sustainable supply chain improvement like the FFP.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some consensus that joint approaches are important for tackling modern slavery, it remains unclear under which conditions exactly such collaboration turns out to be effective. In fact, there are several examples where well-intended multi-stakeholder action does not yield substantial improvements on a systemic scale (Matos et al, 2020), as recently shown for the case of the UK construction sector (Gutierrez-Huerter et al, 2023).…”
Section: Literature and Theorymentioning
confidence: 97%
See 1 more Smart Citation
“…As seen from the different definitions in the Appendix, modern slavery is an umbrella term (Carrington et al, 2021;Nolan & Bott, 2018;Rioux et al, 2020) that is debatable and contentious, and researchers argue that the term does not adequately describe the situation of severe labor exploitation with no clear consensus on which practices or kinds of people would be included under the term (Allain, 2012;Quirk, 2011;Gutierrez-Huerter O et al, 2021;Liu et al, 2022;LeBaron, 2018). More radical scholars even discussed if the term "modern slavery" should be abolished because it describes many forms of unethical practices that cannot be tackled or treated as one specific issue (O'Connell Davidson, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…• The sector is not fully rigorous about enforcing labor standards (CIOB, 2018). • Limited visibility and transparency in lower tiers of the supply chains (Gutierrez-Huerter O et al, 2021). Construction projects are characterized by complex supply chains comprising many subcontractors, suppliers, and labor agencies (Russell et al, 2018;.…”
Section: Structural Conditions Making Construction Projects Prone To ...mentioning
confidence: 99%